The Effects of Color Therapy on Fatigue, Depression, and Quality of Life in Parkinson's Patients: A Randomized Controlled Trial - Coskun, Kubra; Turan, Gulcan Bahcecioglu (Wiley, 2026)
Background When compared with healthy people, fatigue, depression, and a lower quality of life are frequently experienced by Parkinson's patients. Color therapy has effects such as reducing depression and improving focusing problems. Aim Examining the effects of color therapy on fatigue, depression, and quality of life in Parkinson's patients constitutes the aim of the present study. Method This randomized controlled trial was conducted with 60 Parkinson's patients (30 intervention, 30 control). In the first and second weeks, the intervention group received color therapy 3 days per week, consisting of 15-min exposures to purple, yellow, and orange light (totaling 45 min per session). No intervention was performed during the third and fourth weeks. In the fifth and seventh weeks, a single weekly session was administered, applying each color for 15 min (totaling 45 min), while no intervention was carried out in the sixth week. Post-test data were collected in the eighth week. The control group received no intervention. Data collection tools included a Patient Information Form, Parkinson Fatigue Scale (PFS-16), Beck Depression Inventory (BDI), and SF-36 Quality of Life Scale. Results The total mean score and sub-dimension scores of PFS-16 and the total mean score of BDI decreased statistically significantly in the intervention group (p = 0.05). The intervention also caused a significant increase in SF-36 quality of life total score and sub-dimension mean scores of the intervention group (p < 0.05). Conclusion Color therapy application was found to decrease the level of fatigue and depression and improve the quality of life in Parkinson's patients.
Keywords: Color therapy; depression; fatigue; nurse; Parkinson's; Quality of Life